In vitro Efficacy of Beauveria bassiana (Bals.) Vuill. and Verticillium lecanii (Zimm.) viegas against selected insect pests of cotton - Selvanarayanan, A. Karthikeyan*; V. (Recent Research in Science and Technology, 2011)
The bioefficacy of selected entomopathogenic fungi viz. Beauveria bassiana (Bals.) Vuill. against Heliothis armigera Hubner, Spodoptera litura Fabricius, Earias vittella Fabricius and Verticillium lecanii (Zimm.) Viegas against Aphis gossypii Glover, Bemisia tabaci Gennadius and Amrasca devastans Distant was studied under laboratory conditions at Department of Entomology, Faculty of Agriculture, Annamalai University, Annamalainagar, Tamilnadu, India during 2007-2008. Three different concentrations viz., 0.15, 0.20 and 0.25 per cent of liquid formulation of these entomopathogenic fungi were tested to evaluate the effective concentration. Among the three concentrations, 0.25 per cent recorded the highest mortality of H. armigera (86.67 %), S. litura (86.67 %), E. vittella (73.33 %), A. gossypii (100.00 %), B. tabaci (100.00 %) and A. devastansÃ‚Â (93.33 %) respectively.Ã‚Â